Photocuring printing mother-of-pearl alumina composite ceramic based on alumina lamellar crystal adsorption SiO2 and method
By adsorbing SiO2 by alumina sheet crystals and using photocuring 3D printing technology, the problem of difficulty in preparing mother-of-pearl structure mullite-alumina composite ceramics in the existing technology is solved, and the strength and toughness of the ceramics are improved, and its internal structure is optimized.
Patent Information
- Application Number
- CN202510085339.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-20
AI Technical Summary
It is difficult to prepare mullite-alumina composite ceramics with mother-of-pearl structures in the prior art, and it is impossible to effectively regulate the microstructure of the material to improve its mechanical properties.
By adsorbing SiO2 by alumina flakes and using photocuring 3D printing technology, alumina flakes and SiO2 particles are arranged in a directional manner to form mullite-alumina composite ceramics with mother-of-pearl structure.
The preparation of mother-of-pearl structural ceramics is realized, which significantly improves its strength and fracture toughness, and optimizes the internal pore structure and density of the ceramics by adjusting the particle size of SiO2 particles.
Smart Images

Figure CN119797895A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of light-curing additive manufacturing of pearl mother-of-pearl alumina composite ceramics, and specifically relates to a method for manufacturing a nanostructured ... ceramic based on the adsorption of SiO2 by alumina platelets. 2 Photocuring printing of mother-of-pearl alumina composite ceramics, also involves the adsorption of SiO2 by alumina platelets 2 Method for photocuring printing of mother-of-pearl alumina composite ceramics. Background Art
[0002] As a typical structural ceramic, alumina has excellent properties such as high temperature resistance, wear resistance, corrosion resistance and good biocompatibility. It is currently widely used in biomedicine, aerospace, automobile manufacturing and other industries. Alumina composite ceramics not only retain the original physical and chemical properties of alumina, but also further improve its mechanical properties. However, due to the hard and brittle characteristics of alumina itself, its strength and toughness are mutually restricted and cannot be improved synergistically, so it is subject to certain limitations in practical applications.
[0003] Mullite is formed by the reaction of silicon dioxide and aluminum oxide at high temperature. It has the advantages of high temperature stability, high temperature creep resistance, high temperature mechanical properties and excellent chemical stability, but its room temperature mechanical properties are poor. Compounding it with aluminum oxide can make up for its shortcomings. At present, the existing technology can prepare mullite-alumina composite ceramics, but there is no method to further regulate the microstructure of the material. The microstructure of many natural materials is very complex, and there are intricate microstructures at various scales, such as bamboo, mother-of-pearl, etc. The microstructure of these materials can guide the deflection and expansion of cracks and control fractures, producing strength and toughness that exceed the materials that constitute them. In recent years, a large number of studies have combined biological structures with the preparation of ceramic materials to further improve the mechanical properties of ceramic materials, among which the mother-of-pearl bionic structure has attracted the most attention. Summary of the invention
[0004] The first object of the present invention is to provide a method for adsorbing SiO based on alumina platelets. 2 The method of photocuring printing mother-of-pearl alumina composite ceramics solves the current problem that silicon dioxide reacts with alumina at high temperature to form mullite, which makes it impossible to prepare mother-of-pearl structure in mullite composite alumina ceramics, and provides a new method for preparing mother-of-pearl structural ceramics.
[0005] The second object of the present invention is to provide a method for adsorbing SiO based on alumina platelets. 2 Stereolithography printing of mother-of-pearl alumina composite ceramics.
[0006] The first technical solution adopted by the present invention is to adsorb SiO2 on alumina platelets. 2 The method for photocuring printing mother-of-pearl alumina composite ceramics comprises the following steps: 1) SiO 2 The SiO2 and alumina flakes were placed in a beaker filled with distilled water and dispersed evenly. The two solutions were then mixed and stirred with a magnetic stirrer to make the SiO2 2 Fully electrostatically adsorbed with alumina platelets; 2) After the mixed solution is allowed to stand for stratification, the upper clear liquid is removed for vacuum filtration, and then placed in an oven for drying; the dried ceramic powder is pre-sintered to obtain alumina platelets adsorbing SiO 2 ; 3) preparing ceramic slurry; 4) Using the light curing technology, the ceramic slurry prepared in step 3) is irradiated with ultraviolet light, and the SiO adsorbed on the ceramic slurry is made to flow through the slurry. 2 The alumina platelets of the powder are arranged in a directional manner under the action of shear force, and the slurry in the exposed area is quickly solidified by ultraviolet light irradiation, thereby printing out a mother-of-pearl alumina composite ceramic blank; 5) The printed ceramic blank is degreased and sintered under a specific temperature curve. Silicon dioxide reacts with alumina at high temperature to form mullite. The mullite structure is regularly distributed in lamellar shapes along the arrangement direction of the alumina platelets, thereby obtaining an alumina composite ceramic with a mother-of-pearl structure.
[0007] The present invention is also characterized in that: In step 1), the alumina platelets adsorb SiO 2 The composition ratio and mixing time are as follows: 0.5g-1.5g of silicon dioxide should be added to every 30ml of distilled water, and 1g-3g of alumina flakes should be added to every 90ml of distilled water, and then they are placed in an ultrasonic oscillator and mixed for 10 min-30min respectively; then the two solutions are mixed and stirred for 2-3 hours using a digital constant temperature magnetic stirrer; Added SiO 2 The powder is a monodisperse spherical powder with a particle size of 70nm-300nm, an aluminum oxide platelet width of 4μm-15μm, and a thickness of 200nm-300nm.
[0008] In step 2), the standing time is about 30 min-60 min; the adsorbed ceramic powder is dried at a drying temperature of 150° C.-200° C. for 1 h-2 h; A box-type muffle furnace is used in the pre-sintering process, and the sintering process is: room temperature-1200℃ with a heating rate of 20℃ / min-60℃ / min; 1200℃-400℃ with a cooling rate of 1℃ / min-2℃ / min, keeping at 400℃ for 4h-6h, and then cooling with the furnace.
[0009] Step 3) is specifically as follows: first, two dispersants are added to the ceramic slurry liquid phase system and placed in a planetary ball mill for ball milling to completely dissolve the dispersants; then, spherical alumina particle powder and sintering aid are added, and ball milling is continued until the alumina particles are uniformly dispersed in the liquid phase; after removing the grinding balls, the alumina platelets prepared in step 2) are added to adsorb SiO 2 The powder is further dispersed evenly by a ball mill, and then an ultraviolet light initiator is added and stirred evenly, and finally a defoaming treatment is performed under vacuum to obtain a mother-of-pearl alumina composite ceramic slurry.
[0010] In step 3), the ceramic slurry liquid phase system consists of 50-60 vol% of 1,6-hexanediol diacrylate accounting for 50-60 vol% of the total volume of the liquid phase, 30-35 vol% of polypropylene glycol 200 accounting for 30-35 vol% of the total volume of the liquid phase, 5-7.5 vol% of trimethylolpropane triacrylate accounting for 5-7.5 vol% of the total volume of the liquid phase, and 5-7.5 vol% of polyethylene glycol (400) diacrylate accounting for 5-7.5 vol% of the total volume of the liquid phase; Or the ceramic slurry liquid phase system is composed of 1,6-hexanediol diacrylate accounting for 55-65 vol% of the total volume of the liquid phase, polypropylene glycol 400 accounting for 25-35 vol% of the total volume of the liquid phase, and trimethylolpropane triacrylate accounting for 5-10 vol% of the total volume of the liquid phase; The spherical alumina particles added account for 15-30 vol% of the ceramic slurry, and the particle diameter is 1-3 μm. Alumina flakes are added to absorb SiO 2 The powder is 15-30vol% of the ceramic slurry; The added sintering aid is composed of SiO2 adsorbed by alumina platelets. 2 3wt% MgO and CaO powder, the mass ratio of which is 1:1; The two dispersants added are spherical alumina particles and alumina platelets adsorbing SiO 2 The mixing ratio of CC42 and KD1 is 0.4-0.6wt% and 2-3wt% of the total weight of the powder is 1:5; the added UV initiator is TPO accounting for 2 wt% of the mass of the ceramic slurry liquid phase system; the added grinding balls are 6-10 zirconia grinding balls with a diameter of 5mm-15mm per 50ml of slurry.
[0011] In step 4), the exposure time of the light-curing printing process is 3 s -8 s, the light-off time is 2 s -10 s, and the exposure power is 2.48 mW / cm 2 -7.95mW / cm 2 The thickness of each layer is 0.03 mm -0.08 mm, and the lifting speed of the workbench is 0.5 mm / s -1.5 mm / s.
[0012] In step 5), the degreasing process is divided into two parts, first degreasing in an argon atmosphere, and then degreasing in an air atmosphere; The degreasing curve under argon atmosphere is as follows: starting from room temperature, the temperature is increased to 100-130°C at a heating rate of 0.2°C / min-0.5°C / min, and the temperature is kept for 600-700min; the temperature is increased to 220-250°C at a heating rate of 0.2°C / min-0.5°C / min, and the temperature is kept for 600-700min; the temperature is increased to 310-340°C at a heating rate of 0.2°C / min-0.5°C / min, and the temperature is kept for 600-700min; the temperature is decreased to 100°C at a cooling rate of 2°C / min-4°C / min, and then cooled with the furnace; The degreasing curve in air atmosphere is: starting from room temperature, adopt a heating rate of 0.3-0.6℃ / min to increase to 100℃-130℃ and keep warm for 120 min-220min, adopt a heating rate of 0.3℃ / min-0.6℃ / min to increase to 220℃-250℃ and keep warm for 120 min-220min, adopt a heating rate of 0.3℃ / min-0.6℃ / min to increase to 310℃-340℃ and keep warm for 240min-340min, adopt a heating rate of 0.3℃ / min-0.6℃ / min to increase to 370℃-400℃ and keep warm for 240 min-340min, adopt a heating rate of 0.3℃ / min-0.6℃ / min to increase to 600℃-700℃, adopt a heating rate of 0.5℃ / min-1℃ / min to increase to 1000℃, adopt a heating rate of 2℃ / min The temperature was lowered to 100°C at a rate of -4°C / min and then cooled in the furnace.
[0013] In step 5), sintering is carried out in an air atmosphere sintering furnace, and the specific sintering curve is: room temperature-1200°C adopts a heating rate of 4°C / min-4.5°C / min, 1200°C-1650°C adopts a heating rate of 3°C / min-3.5°C / min, 1650°C is kept for 120min-180min, 1650°C-1200°C adopts a cooling rate of 3°C / min-4°C / min, 1200°C-500°C adopts a cooling rate of 4°C / min-5°C / min, and then the furnace is cooled.
[0014] The second technical solution adopted by the present invention is to adsorb SiO2 on the alumina platelets. 2 The photocuring printed mother-of-pearl alumina composite ceramics were prepared by the above method.
[0015] The beneficial effects of the present invention are: The method of the present invention can attach silica particles on the surface of alumina platelets by electrostatic adsorption, and then use the shear force generated when the slurry flows during the light-curing 3D printing process to make the alumina platelets adsorbing silica arranged in a directional manner to prepare mother-of-pearl alumina composite ceramics, and after the prepared ceramic blank is sintered, the silica particles react with alumina at a high temperature to generate mullite, and the mullite structure is regularly distributed in a lamellar shape along the arrangement direction of the alumina platelets. Thus, the purpose of using mullite composite alumina ceramics to prepare mother-of-pearl structures is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a flow chart of the method of the present invention; Figure 2 is a scanning electron microscope image of the aluminum oxide platelet crystal used in Example 1 of the method of the present invention; Figure 3 is a scanning electron microscope image of silicon dioxide used in Example 1 of the method of the present invention; Figure 4 This is a scanning electron microscope image of silicon dioxide adsorbed on alumina platelets prepared in Example 1 of the method of the present invention; Figure 5 is a scanning electron microscope image of a cross section of the mother-of-pearl composite ceramic of Example 1 in the method of the present invention; Figure 6 This is a scanning electron microscope image of silicon dioxide adsorbed on alumina platelets prepared in Example 3 of the method of the present invention; Figure 7 It is a scanning electron microscope image of the cross section of the mother-of-pearl composite ceramic in Example 3 of the method of the present invention. DETAILED DESCRIPTION
[0017] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0018] The present invention provides a method for adsorbing SiO based on aluminum oxide flakes. 2 Methods for photocuring printing of mother-of-pearl alumina composite ceramics, such as Figure 1 As shown, the following steps are included: 1) SiO 2 The SiO2 and alumina flakes were placed in a beaker filled with distilled water and dispersed evenly. The two solutions were then mixed and stirred with a magnetic stirrer to make the SiO2 2 Fully electrostatically adsorbed with alumina platelets; In step 1), the alumina platelets adsorb SiO 2 The composition ratio and mixing time are as follows: 0.5-1.5g of silicon dioxide should be added to every 30ml of distilled water, and 1-3g of alumina flakes should be added to every 90ml of distilled water, and then they are placed in a DSA50-SK-1 ultrasonic oscillator and mixed for 10-30min; then the two solutions are mixed and stirred for 2-3 hours using a digital constant temperature magnetic stirrer; Added SiO 2 The powder is a monodisperse spherical powder with a particle size of 70-300nm, a width of 4-15μm, and a thickness of 200-300nm. 2) After the mixed solution is allowed to stand for stratification, the upper clear liquid is removed for vacuum filtration, and then placed in an oven for drying; the dried ceramic powder is pre-sintered to obtain alumina platelets adsorbing SiO 2 ; In step 2), the standing time is about 30-60 minutes; the adsorbed ceramic powder is dried at a drying temperature of 150-200° C. for 1-2 hours; The pre-sintering process uses a box-type muffle furnace, and the sintering process is: room temperature-1200℃ with a heating rate of 20-60℃ / min; 1200℃-400℃ with a cooling rate of 1-2℃ / min, 400℃ insulation for 4-6h, and then cooling with the furnace; 3) Preparation of ceramic slurry: First, prepare a ceramic slurry liquid phase system, then add two dispersants into the ceramic slurry liquid phase system and put it into a planetary ball mill for ball milling to completely dissolve the dispersants; then add spherical alumina particle powder and sintering aid, and continue ball milling until the alumina particles are evenly dispersed in the liquid phase; remove the grinding balls and add the alumina platelets prepared above to absorb SiO 2 The powder is further dispersed evenly by a ball mill, and then an ultraviolet light initiator is added and stirred evenly, and finally a defoaming treatment is performed under vacuum to obtain a mother-of-pearl alumina composite ceramic slurry; In step 3), the ceramic slurry liquid phase system consists of 50-60 vol% of 1,6-hexanediol diacrylate accounting for 50-60 vol% of the total volume of the liquid phase, 30-35 vol% of polypropylene glycol 200 accounting for 30-35 vol% of the total volume of the liquid phase, 5-7.5 vol% of trimethylolpropane triacrylate accounting for 5-7.5 vol% of the total volume of the liquid phase, and 5-7.5 vol% of polyethylene glycol (400) diacrylate accounting for 5-7.5 vol% of the total volume of the liquid phase; Or the ceramic slurry liquid phase system consists of 55-65 vol% of 1,6-hexanediol diacrylate accounting for the total volume of the liquid phase, 25-35 vol% of polypropylene glycol 400 accounting for the total volume of the liquid phase, and 5-10 vol% of trimethylolpropane triacrylate accounting for the total volume of the liquid phase; The ceramic slurry liquid phase system is prepared by mixing the raw materials of the above formula.
[0019] The amount of spherical alumina particles added is 15-30 vol% of the ceramic slurry, and the particle diameter is 1-3 μm. Alumina flakes are added to absorb SiO 2 The powder is 15-30vol% of the ceramic slurry; The added sintering aid is composed of SiO2 adsorbed by alumina platelets.2 3 wt% of MgO and CaO in powder, the mass ratio of which is 1:1; The two dispersants added are spherical alumina particles and alumina platelets adsorbing SiO 2 The mixing ratio of CC42 is 0.4-0.6wt% and KD1 is 2-3wt% of the total weight of the powder, and the mixing ratio is 1:5; the added ultraviolet light initiator is TPO accounting for 2 wt% of the mass of the ceramic slurry liquid phase system.
[0020] The ratio of grinding balls added is 6-10 zirconia grinding balls with a diameter of 5-15 mm per 50 ml of slurry.
[0021] 4) Using light curing technology, the slurry flows to absorb SiO 2 The alumina platelets of the powder are arranged in a directional manner under the action of shear force, and the slurry in the exposed area is quickly solidified by ultraviolet light irradiation, thereby printing out a mother-of-pearl alumina composite ceramic blank; In step 4), the exposure time of the light-curing printing process is 3-7s, the light-off time is 2-10s, and the exposure power is 2.48-7.95mW / cm 2 , the thickness of each layer is 0.03-0.08mm, and the lifting speed of the workbench is 0.5-1.5mm / s; 5) The printed ceramic blank is degreased and sintered under a specific temperature curve. Silicon dioxide reacts with alumina at high temperature to form mullite. The mullite structure is regularly distributed in lamellar shapes along the arrangement direction of alumina lamellae, thereby obtaining alumina composite ceramics with a mother-of-pearl structure. In step 5), the degreasing process is divided into two parts, first degreasing in an argon atmosphere, and then degreasing in an air atmosphere; The degreasing curve under argon atmosphere is: starting from room temperature, heating up to 100℃-130℃ at a heating rate of 0.2-0.5℃ / min and keeping the temperature for 600-700min, heating up to 220℃-250℃ at a heating rate of 0.2-0.5℃ / min and keeping the temperature for 600-700min, heating up to 310℃-340℃ at a heating rate of 0.2-0.5℃ / min and keeping the temperature for 600-700min, cooling down to 100℃ at a cooling rate of 2-4℃ / min, and then cooling with the furnace; The degreasing curve in air atmosphere is: starting from room temperature, heating up to 100℃-130℃ at a heating rate of 0.3-0.6℃ / min and keeping warm for 120-220min, heating up to 220℃-250℃ at a heating rate of 0.3-0.6℃ / min and keeping warm for 120-220min, heating up to 310℃-340℃ at a heating rate of 0.3-0.6℃ / min and keeping warm for 240-340min, heating up to 370℃-400℃ at a heating rate of 0.3-0.6℃ / min and keeping warm for 240-340min, heating up to 600℃-700℃ at a heating rate of 0.3-0.6℃ / min, heating up to 1000℃ at a heating rate of 0.5-1℃ / min, cooling down to 100℃ at a cooling rate of 2-4℃ / min, and then cooling with the furnace; The sintering is carried out in an air atmosphere sintering furnace. The specific sintering curve is: a heating rate of 4-4.5°C / min from room temperature to 1200°C, a heating rate of 3-3.5°C / min from 1200°C to 1650°C, keeping at 1650°C for 120-180min, a cooling rate of 3-4°C / min from 1650°C to 1200°C, a cooling rate of 4-5°C / min from 1200°C to 500°C, and then cooling with the furnace.
[0022] The present invention also provides a method for adsorbing SiO based on alumina platelets. 2 The photocuring printed mother-of-pearl alumina composite ceramics were prepared by the above method.
[0023] Example 1 1) Add 0.5g of silica with a particle diameter of 300nm into a beaker containing 15ml of distilled water. Take another clean beaker, add 2g of alumina flakes with a width of 10μm and a thickness of 200nm into 90ml of distilled water, and put them into a DSA50-SK-1 ultrasonic oscillator for mixing for 10min. Then mix the two evenly dispersed solutions and stir them for 2 hours using a digital constant temperature magnetic stirrer to allow the alumina flakes to be fully electrostatically adsorbed with silica. 2) The solution prepared in step 1) was allowed to stand for 30 min, and after the solution was separated into layers, the upper clear liquid was poured out for vacuum filtration. After the filtration, the adsorbed ceramic powder was placed in an oven and kept at 150°C for 1 h; then the dried ceramic powder was placed in a box-type muffle furnace, and the temperature was increased to 1200°C at a heating rate of 50°C / min, and then the temperature was reduced to 400°C at a rate of 1.7°C / min and kept at this temperature for 4 h, and then cooled with the furnace; 3) 50 vol% of 1,6-hexanediol diacrylate, 35 vol% of polypropylene glycol 200, 7.5 vol% of trimethylolpropane triacrylate, and 7.5 vol% of polyethylene glycol (400) diacrylate were mixed to prepare a ceramic slurry liquid phase system, and then spherical alumina particle powder and alumina platelets adsorbing SiO 2 0.5wt% CC42 and 2.5wt% KD1 of the total weight of the powder are used as dispersants, and then put into a planetary ball mill for 6h to completely dissolve the dispersants; then spherical alumina particle powder (powder diameter is 1μm) accounting for 24.75vol% of the ceramic slurry and MgO and CaO (the mass ratio of MgO to CaO is 1:1) accounting for 3wt% of the alumina platelet adsorbed silica powder are added as sintering aids and the ball milling is continued for 2h to make it evenly dispersed; then the grinding ball is taken out, and the alumina platelet adsorbed SiO prepared in step 2) accounting for 20.25vol% of the ceramic slurry is added. 2 The ball milling was continued for 2 hours to make the mixture uniform, and then 2 wt% of TPO accounting for the mass of the ceramic slurry liquid phase system was added as a UV initiator and the stirring was continued for 10 minutes. Finally, the mixture was defoamed under vacuum to obtain a mother-of-pearl alumina composite ceramic slurry. The ratio of the added grinding balls is 4 zirconia grinding balls with a diameter of 10 mm and 4 zirconia grinding balls with a diameter of 5 mm per 50 ml of slurry.
[0024] 4) Using the light-curing 3D printing technology, pour the prepared slurry into the slurry tank of the printer, and the slurry flows to absorb the SiO 2 The aluminum oxide flakes in the powder are oriented under the action of shear force. When the exposure time is 5s, the light is turned off for 2s, and the exposure power is 2.48 mW / cm 2 Under the irradiation of ultraviolet light, the ceramic slurry in the exposure area quickly solidifies and adheres to the printing platform. The thickness of each layer is 0.05mm. After each layer of pattern is exposed, the printing platform rises at a speed of 1mm / s, and then the next layer is exposed. 5) Degreasing and sintering the printed ceramic blank. The degreasing process is divided into two parts: first, degreasing in an argon atmosphere, and then degreasing in an air atmosphere; The debinding curve in argon atmosphere is as follows: starting from room temperature, the temperature is increased to 103°C at a rate of 0.2°C / min and kept at 103°C for 600 min, the temperature is increased to 220°C at a rate of 0.2°C / min and kept at 220°C for 600 min, the temperature is increased to 310°C at a rate of 0.2°C / min and kept at 310°C for 600 min, the temperature is decreased to 100°C at a rate of 2°C / min, and then cooled in the furnace; The degreasing curve in air atmosphere is: starting from room temperature, heating up to 103℃ at a heating rate of 0.4℃ / min and keeping it for 120min, heating up to 220℃ at a heating rate of 0.4℃ / min and keeping it for 120min, heating up to 310℃ at a heating rate of 0.4℃ / min and keeping it for 240min, heating up to 370℃ at a heating rate of 0.4℃ / min and keeping it for 240min, heating up to 600℃ at a heating rate of 0.4℃ / min, heating up to 1000℃ at a heating rate of 0.7℃ / min, cooling down to 100℃ at a cooling rate of 3℃ / min, and then cooling with the furnace; The sintering was carried out in an air atmosphere sintering furnace. The specific sintering curve was as follows: a heating rate of 4°C / min from room temperature to 1200°C, a heating rate of 3°C / min from 1200°C to 1650°C, keeping at 1650°C for 120 min, a cooling rate of 3°C / min from 1650°C to 1200°C, a cooling rate of 4°C / min from 1200°C to 500°C, and then cooling with the furnace.
[0025] from Figure 2 It can be seen that the alumina platelets have obvious lamellar structural characteristics and a large diameter-to-thickness ratio; Figure 3 It can be seen that the silicon dioxide is a submicron spherical powder.
[0026] like Figure 4 The figure shows a scanning electron microscope image of the aluminum oxide platelet prepared in Example 1 adsorbing silicon dioxide. It can be seen from the figure that the silicon dioxide particles are adsorbed on the surface of the aluminum oxide platelet by electrostatic adsorption. Figure 5 This is a scanning electron microscope image of the cross section of the mother-of-pearl composite ceramic printed by the light-curing additive manufacturing technology in Example 1. It can be seen from the image that the aluminum oxide platelets and SiO 2 The reaction occurs to generate a lamellar mullite reinforcement with a high aspect ratio. Due to the Oswald effect, the mullite structure generated by the reaction maintains the arrangement direction of the original lamellar crystals to form a mother-of-pearl structure.
[0027] Example 2 1) Add 0.5g of silica with a particle diameter of 150nm into a beaker containing 15ml of distilled water. Take another clean beaker, add 2g of alumina flakes with a width of 10μm and a thickness of 300nm into 90ml of distilled water, and put them into a DSA50-SK-1 ultrasonic oscillator for mixing for 10min. Then mix the two evenly dispersed solutions and stir them for 2 hours using a digital constant temperature magnetic stirrer to allow the alumina flakes to be fully electrostatically adsorbed with silica. 2) The solution prepared in step 1) was allowed to stand for 30 min, and after the solution was separated into layers, the upper clear liquid was poured out for vacuum filtration. After the filtration, the adsorbed ceramic powder was placed in an oven and kept at 150°C for 1 h; then the dried ceramic powder was placed in a box-type muffle furnace, and the temperature was increased to 1200°C at a rate of 40°C / min, and then the temperature was reduced to 400°C at a rate of 1.5°C / min and kept at this temperature for 4 h, and then cooled with the furnace; Step 3 is the same as in Example 1; 4) Using the light-curing 3D printing technology, pour the prepared slurry into the slurry tank of the printer, and the slurry flows to absorb the SiO 2 The aluminum oxide flakes in the powder are oriented under the action of shear force. When the exposure time is 6s, the light is turned off for 3s, and the exposure power is 2.48 mW / cm 2 Under the irradiation of ultraviolet light, the ceramic slurry in the exposure area quickly solidifies and adheres to the printing platform. The thickness of each layer is 0.06mm. After each layer of pattern is exposed, the printing platform rises at a speed of 1mm / s, and then the next layer is exposed. 5) Degreasing and sintering the printed ceramic blank. The degreasing process is divided into two parts: first, degreasing in an argon atmosphere, and then degreasing in an air atmosphere; The debinding curve in argon atmosphere is as follows: starting from room temperature, the temperature is increased to 103°C at a heating rate of 0.3°C / min and kept for 600 min; the temperature is increased to 220°C at a heating rate of 0.3°C / min and kept for 600 min; the temperature is increased to 310°C at a heating rate of 0.3°C / min and kept for 600 min; the temperature is decreased to 100°C at a cooling rate of 2°C / min, and then cooled with the furnace; The degreasing curve in air atmosphere is: starting from room temperature, heating up to 103℃ at a heating rate of 0.4℃ / min and keeping it for 120min, heating up to 220℃ at a heating rate of 0.4℃ / min and keeping it for 120min, heating up to 310℃ at a heating rate of 0.4℃ / min and keeping it for 240min, heating up to 370℃ at a heating rate of 0.4℃ / min and keeping it for 240min, heating up to 600℃ at a heating rate of 0.4℃ / min, heating up to 1000℃ at a heating rate of 0.7℃ / min, cooling down to 100℃ at a cooling rate of 3℃ / min, and then cooling with the furnace; The sintering was carried out in an air atmosphere sintering furnace. The specific sintering curve was as follows: a heating rate of 4°C / min from room temperature to 1200°C, a heating rate of 3°C / min from 1200°C to 1650°C, keeping at 1650°C for 120 min, a cooling rate of 3°C / min from 1650°C to 1200°C, a cooling rate of 4°C / min from 1200°C to 500°C, and then cooling with the furnace.
[0028] Example 3 1) Add 0.35g of silica with a particle diameter of 300nm into a beaker containing 15ml of distilled water. Take another clean beaker, add 2g of alumina flakes with a width of 10μm and a thickness of 250-300nm into 90ml of distilled water, and put them into a DSA50-SK-1 ultrasonic oscillator for mixing for 10min. Then mix the two evenly dispersed solutions and stir them for 2 hours using a digital constant temperature magnetic stirrer to allow the alumina flakes to be fully electrostatically adsorbed with silica. Step 2 is the same as in Example 2; 3) 60 vol% of 1,6-hexanediol diacrylate, 30 vol% of polypropylene glycol 400, and 10 vol% of trimethylolpropane triacrylate were mixed to prepare a ceramic slurry liquid phase system, and then spherical alumina particle powder and alumina platelets adsorbing SiO 2 0.5wt% CC42 and 2.5wt% KD1 of the total weight of the powder are used as dispersants, and then put into a planetary ball mill for 6h to completely dissolve the dispersants; then 29.25vol% of spherical alumina particle powder (powder diameter is 3μm) accounting for 29.25vol% of the ceramic slurry and 3wt% of MgO and CaO (the mass ratio of MgO to CaO is 1:1) accounting for 3wt% of the alumina platelet adsorbed silica powder are added as sintering aids and the ball milling is continued for 2h to make it evenly dispersed; then the grinding ball is taken out, and the alumina platelet adsorbed SiO prepared in step 3) accounting for 15.75vol% of the ceramic slurry is added. 2 The ball milling was continued for 2 h to make the mixture uniformly mixed, and finally 2 wt% of TPO as a UV initiator was added to the ceramic slurry liquid phase system, and the mixture was stirred for 10 min, and then defoamed under vacuum to obtain a ceramic slurry. The ratio of the added grinding balls is 5 zirconia grinding balls with a diameter of 10 mm and 3 zirconia grinding balls with a diameter of 5 mm per 50 ml of slurry.
[0029] Step 4 is the same as in Example 2; 5) Degreasing and sintering the printed ceramic blank. The degreasing process is divided into two parts: first, degreasing in an argon atmosphere, and then degreasing in an air atmosphere; The debinding curve in argon atmosphere is as follows: starting from room temperature, the temperature is increased to 103°C at a rate of 0.2°C / min and kept at 103°C for 600 min, the temperature is increased to 220°C at a rate of 0.2°C / min and kept at 220°C for 600 min, the temperature is increased to 310°C at a rate of 0.2°C / min and kept at 310°C for 600 min, the temperature is decreased to 100°C at a rate of 2°C / min, and then cooled in the furnace; The degreasing curve in air atmosphere is: starting from room temperature, heating up to 103℃ at a heating rate of 0.3℃ / min and keeping it for 120min, heating up to 220℃ at a heating rate of 0.3℃ / min and keeping it for 120min, heating up to 310℃ at a heating rate of 0.3℃ / min and keeping it for 240min, heating up to 370℃ at a heating rate of 0.3℃ / min and keeping it for 240min, heating up to 600℃ at a heating rate of 0.3℃ / min, heating up to 1000℃ at a heating rate of 0.5℃ / min, cooling down to 100℃ at a cooling rate of 2℃ / min, and then cooling with the furnace; The sintering was carried out in an air atmosphere sintering furnace. The specific sintering curve was as follows: a heating rate of 4°C / min from room temperature to 1200°C, a heating rate of 3°C / min from 1200°C to 1650°C, keeping at 1650°C for 120 min, a cooling rate of 3°C / min from 1650°C to 1200°C, a cooling rate of 4°C / min from 1200°C to 500°C, and then cooling with the furnace.
[0030] like Figure 6 The figure shows a scanning electron microscope image of silicon dioxide adsorbed by aluminum oxide platelets prepared in Example 3. Compared with Example 1, the silicon dioxide content is reduced, so the silicon dioxide particles adsorbed by the aluminum oxide platelets are reduced. Figure 7 This is a scanning electron microscope image of the cross section of the mother-of-pearl composite ceramic printed by the light-curing additive manufacturing technology in Example 3. Compared with Example 1, it can be seen that as the content of silicon dioxide adsorbed by the alumina platelets increases, the pores inside the ceramic will increase.
[0031] Example 4 1) Add 1g of silica with a particle diameter of 200nm into a beaker containing 20ml of distilled water. Take another clean beaker, add 2g of alumina flakes with a width of 10μm and a thickness of 200nm into 90ml of distilled water, and put them into a DSA50-SK-1 ultrasonic oscillator for mixing for 20min. Then mix the two evenly dispersed solutions and stir them for 2 hours using a digital constant temperature magnetic stirrer to allow the alumina flakes to be fully electrostatically adsorbed with silica. 2) The solution prepared in step 1) was allowed to stand for 30 min, after the solution was separated into layers, the upper clear liquid was poured out for vacuum filtration, and after filtration, the adsorbed ceramic powder was placed in an oven and kept at 150°C for 1 h; then the dried ceramic powder was placed in a box-type muffle furnace, and the temperature was increased to 1200°C at a rate of 50°C / min, and then the temperature was reduced to 400°C at a rate of 1.7°C / min and kept at this temperature for 4 h, and then cooled with the furnace; Step 3 is the same as in Example 3; 4) Using the light-curing 3D printing technology, pour the prepared slurry into the slurry tank of the printer, and the slurry flows to absorb the SiO 2 The aluminum oxide flakes in the powder are oriented under the action of shear force. When the exposure time is 6s, the light is turned off for 2s, and the exposure power is 2.48 mW / cm 2 Under the irradiation of ultraviolet light, the ceramic slurry in the exposure area quickly solidifies and adheres to the printing platform. The thickness of each layer is 0.07mm. After each layer of pattern is exposed, the printing platform rises at a speed of 1mm / s, and then the next layer is exposed. Step 5 is the same as in Example 3; Compared with traditional alumina ceramics, the pearl alumina composite ceramics printed by the method of the present invention have greatly improved strength and fracture toughness. 2 With the addition of silicon dioxide, pores will appear inside the ceramic, reducing the density. In addition, the strength and toughness of the printed mother-of-pearl alumina composite ceramics will also be different due to the different particle sizes of the adsorbed silicon dioxide. Therefore, in practical applications, the appropriate particle size can be selected according to different scenarios.
[0032] Example 5 1) Add 0.25g of silica with a particle diameter of 70nm into a beaker containing 15ml of distilled water. Take another clean beaker, add 1g of alumina flakes with a width of 4μm and a thickness of 200nm into 90ml of distilled water, and put them into a DSA50-SK-1 ultrasonic oscillator for mixing for 10min. Then mix the two evenly dispersed solutions and stir them for 2 hours using a digital constant temperature magnetic stirrer to allow the alumina flakes to be fully electrostatically adsorbed with silica. 2) The solution prepared in step 1) was allowed to stand for 30 min, and after the solution was separated into layers, the upper clear liquid was poured out for vacuum filtration. After the filtration, the adsorbed ceramic powder was placed in an oven and kept at 150°C for 1 h; then the dried ceramic powder was placed in a box-type muffle furnace, and the temperature was increased to 1200°C at a rate of 20°C / min, and then the temperature was reduced to 400°C at a rate of 1°C / min and kept at this temperature for 4 h, and then cooled with the furnace; 3) 50 vol% of 1,6-hexanediol diacrylate, 35 vol% of polypropylene glycol 200, 7.5 vol% of trimethylolpropane triacrylate, and 7.5 vol% of polyethylene glycol (400) diacrylate were mixed to prepare a ceramic slurry liquid phase system, and then spherical alumina particle powder and alumina platelets adsorbing SiO 20.4wt% CC42 and 2wt% KD1 of the total weight of the powder are used as dispersants, and then put into a planetary ball mill for 6h to completely dissolve the dispersants; then 20vol% of spherical alumina particle powder (powder diameter is 2μm) accounting for 20vol% of the ceramic slurry and 3wt% of MgO and CaO (the mass ratio of MgO to CaO is 1:1) accounting for alumina platelets adsorbed silica powder are added as sintering aids and the ball milling is continued for 2h to make it evenly dispersed; then the grinding ball is taken out, and the alumina platelets adsorbed SiO prepared in step 2) accounting for 30vol% of the ceramic slurry are added. 2 The ball milling was continued for 2 hours to make the mixture uniform, and then 2 wt% of TPO accounting for the mass of the ceramic slurry liquid phase system was added as a UV initiator and the stirring was continued for 10 minutes. Finally, the mixture was defoamed under vacuum to obtain a mother-of-pearl alumina composite ceramic slurry. The ratio of the added grinding balls is 8 zirconia grinding balls with a diameter of 15 mm per 50 ml of slurry.
[0033] 4) Using the light-curing 3D printing technology, pour the prepared slurry into the slurry tank of the printer, and the slurry flows to absorb the SiO 2 The aluminum oxide flakes in the powder are oriented under the action of shear force. When the exposure time is 3s, the light is turned off for 2s, and the exposure power is 2.48 mW / cm 2 Under the irradiation of ultraviolet light, the ceramic slurry in the exposure area quickly solidifies and adheres to the printing platform. The thickness of each layer is 0.08mm. After each layer of pattern is exposed, the printing platform rises at a speed of 0.5mm / s, and then the next layer is exposed. 5) Degreasing and sintering the printed ceramic blank. The degreasing process is divided into two parts: first, degreasing in an argon atmosphere, and then degreasing in an air atmosphere; The degreasing curve in argon atmosphere is as follows: starting from room temperature, heating up to 100°C at a rate of 0.2°C / min and keeping the temperature for 600 min, heating up to 220°C at a rate of 0.2°C / min and keeping the temperature for 600 min, heating up to 310°C at a rate of 0.2°C / min and keeping the temperature for 600 min, cooling down to 100°C at a rate of 2°C / min, and then cooling with the furnace; The degreasing curve in air atmosphere is: starting from room temperature, heating up to 100℃ at a heating rate of 0.3℃ / min and keeping it for 120min, heating up to 220℃ at a heating rate of 0.3℃ / min and keeping it for 120min, heating up to 310℃ at a heating rate of 0.3℃ / min and keeping it for 240min, heating up to 370℃ at a heating rate of 0.3℃ / min and keeping it for 240min, heating up to 600℃ at a heating rate of 0.3℃ / min, heating up to 1000℃ at a heating rate of 0.5℃ / min, cooling down to 100℃ at a cooling rate of 2℃ / min, and then cooling with the furnace; The sintering was carried out in an air atmosphere sintering furnace. The specific sintering curve was as follows: a heating rate of 4°C / min from room temperature to 1200°C, a heating rate of 3°C / min from 1200°C to 1650°C, keeping at 1650°C for 120 min, a cooling rate of 3°C / min from 1650°C to 1200°C, a cooling rate of 4°C / min from 1200°C to 500°C, and then cooling with the furnace.
[0034] Example 6 1) Add 0.5g of silica with a particle diameter of 185nm into a beaker containing 15ml of distilled water. Take another clean beaker, add 2g of alumina flakes with a width of 10μm and a thickness of 250nm into 90ml of distilled water, and put them into a DSA50-SK-1 ultrasonic oscillator for mixing for 20min. Then mix the two evenly dispersed solutions and stir them for 2.5 hours using a digital constant temperature magnetic stirrer to allow the alumina flakes to be fully electrostatically adsorbed with silica. 2) The solution prepared in step 1) was allowed to stand for 45 min, and after the solution was separated into layers, the upper clear liquid was poured out for vacuum filtration. After the filtration, the adsorbed ceramic powder was placed in an oven and kept at 175°C for 1.5 h; then the dried ceramic powder was placed in a box-type muffle furnace, and the temperature was increased to 1200°C at a rate of 40°C / min, and then the temperature was reduced to 400°C at a rate of 1.5°C / min and kept at this temperature for 5 h, and then cooled with the furnace; 3) 55 vol% of 1,6-hexanediol diacrylate, 35 vol% of polypropylene glycol 200, 5 vol% of trimethylolpropane triacrylate, and 5 vol% of polyethylene glycol (400) diacrylate were mixed to prepare a ceramic slurry liquid phase system, and then spherical alumina particle powder and alumina platelets adsorbing SiO 20.5wt% CC42 and 2.5wt% KD1 of the total weight of the powder are used as dispersants, and then put into a planetary ball mill for 6h to completely dissolve the dispersants; then 25vol% of spherical alumina particle powder (powder diameter is 2μm) accounting for the ceramic slurry and 3wt% of MgO and CaO accounting for the alumina platelet adsorbed silica powder are added as sintering aids and the ball milling is continued for 2h to make it evenly dispersed; then the grinding ball is taken out, and the alumina platelet adsorbed SiO2 powder accounting for 25vol% of the ceramic slurry prepared in step 2) is added. 2 The ball milling was continued for 2 hours to make the mixture uniform, and then 2 wt% of TPO accounting for the mass of the ceramic slurry liquid phase system was added as a UV initiator and the stirring was continued for 10 minutes. Finally, the mixture was defoamed under vacuum to obtain a mother-of-pearl alumina composite ceramic slurry. The ratio of the added grinding balls is 10 zirconia grinding balls with a diameter of 8 mm per 50 ml of slurry.
[0035] 4) Using the light-curing 3D printing technology, pour the prepared slurry into the slurry tank of the printer, and the slurry flows to absorb the SiO 2 The alumina platelets of the powder are oriented under the action of shear force. When the exposure time is 5s, the light off time is 6s, and the exposure power is 5.22 mW / cm 2 Under the irradiation of ultraviolet light, the ceramic slurry in the exposure area quickly solidifies and adheres to the printing platform. The thickness of each layer is 0.06mm. After each layer of pattern is exposed, the printing platform rises at a speed of 1mm / s, and then the next layer is exposed. 5) Degreasing and sintering the printed ceramic blank. The degreasing process is divided into two parts: first, degreasing in an argon atmosphere, and then degreasing in an air atmosphere; The debinding curve in argon atmosphere is as follows: starting from room temperature, the temperature is increased to 115°C at a rate of 0.35°C / min and kept at 115°C for 650 min, the temperature is increased to 235°C at a rate of 0.35°C / min and kept at 235°C for 650 min, the temperature is increased to 325°C at a rate of 0.35°C / min and kept at 325°C for 650 min, the temperature is decreased to 100°C at a rate of 3°C / min, and then cooled in the furnace; The degreasing curve in air atmosphere is: starting from room temperature, heating up to 115℃ at a heating rate of 0.45℃ / min and keeping it for 170min, heating up to 235℃ at a heating rate of 0.45℃ / min and keeping it for 170min, heating up to 325℃ at a heating rate of 0.45℃ / min and keeping it for 290min, heating up to 385℃ at a heating rate of 0.45℃ / min and keeping it for 290min, heating up to 650℃ at a heating rate of 0.45℃ / min, heating up to 1000℃ at a heating rate of 0.75℃ / min, cooling down to 100℃ at a cooling rate of 3℃ / min, and then cooling with the furnace; The sintering was carried out in an air atmosphere sintering furnace. The specific sintering curve was as follows: a heating rate of 4.25°C / min from room temperature to 1200°C, a heating rate of 3.25°C / min from 1200°C to 1650°C, keeping at 1650°C for 150min, a cooling rate of 3.5°C / min from 1650°C to 1200°C, a cooling rate of 4.5°C / min from 1200°C to 500°C, and then cooling with the furnace.
[0036] Example 7 1) Add 0.75g of silica with a particle diameter of 300nm into a beaker containing 15ml of distilled water. Take another clean beaker, add 3g of alumina flakes with a width of 15μm and a thickness of 300nm into 90ml of distilled water, and put them into a DSA50-SK-1 ultrasonic oscillator for mixing for 30min. Then mix the two evenly dispersed solutions and stir them for 3 hours using a digital constant temperature magnetic stirrer to allow the alumina flakes to be fully electrostatically adsorbed with silica. 2) The solution prepared in step 1) was allowed to stand for 60 min, and after the solution was separated into layers, the upper clear liquid was poured out for vacuum filtration. After the filtration, the adsorbed ceramic powder was placed in an oven and kept at 200°C for 2 h; then the dried ceramic powder was placed in a box-type muffle furnace, and the temperature was increased to 1200°C at a rate of 60°C / min, and then the temperature was reduced to 400°C at a rate of 2°C / min and kept at this temperature for 6 h, and then cooled with the furnace; 3) 60 vol% of 1,6-hexanediol diacrylate, 30 vol% of polypropylene glycol 200, 5 vol% of trimethylolpropane triacrylate, and 5 vol% of polyethylene glycol (400) diacrylate were mixed to prepare a ceramic slurry liquid phase system, and then spherical alumina particle powder and alumina platelets adsorbing SiO 2 0.6wt% CC42 and 3wt% KD1 of the total weight of the powder are used as dispersants, and then put into a planetary ball mill for 6h to completely dissolve the dispersants; then 30vol% of spherical alumina particle powder (powder diameter is 1μm) accounting for 30vol% of the ceramic slurry and 3wt% of MgO and CaO (the mass ratio of MgO to CaO is 1:1) accounting for 3wt% of the alumina platelet adsorbed silica powder are added as sintering aids and the ball milling is continued for 2h to make it evenly dispersed; then the grinding ball is taken out, and the alumina platelet adsorbed SiO prepared in step 2) accounting for 20vol% of the ceramic slurry is added 2 The ball milling was continued for 2 hours to make the mixture uniform, and then 2 wt% of TPO accounting for the mass of the ceramic slurry liquid phase system was added as a UV initiator and the stirring was continued for 10 minutes. Finally, the mixture was defoamed under vacuum to obtain a mother-of-pearl alumina composite ceramic slurry. The ratio of grinding balls added is 6 zirconia grinding balls with a diameter of 5 mm per 50 ml of slurry.
[0037] 4) Using the light-curing 3D printing technology, pour the prepared slurry into the slurry tank of the printer, and the slurry flows to absorb the SiO 2 The aluminum oxide flakes in the powder are oriented under the action of shear force. When the exposure time is 7s, the light is turned off for 10s, and the exposure power is 7.95 mW / cm 2 Under the irradiation of ultraviolet light, the ceramic slurry in the exposed area quickly solidifies and adheres to the printing platform. The thickness of each layer is 0.09mm. After each layer of pattern is exposed, the printing platform rises at a speed of 1.5mm / s, and then the next layer is exposed. 5) Degreasing and sintering the printed ceramic blank. The degreasing process is divided into two parts: first, degreasing in an argon atmosphere, and then degreasing in an air atmosphere; The debinding curve in argon atmosphere is as follows: starting from room temperature, the temperature is increased to 130°C at a heating rate of 0.5°C / min and kept at 700min, the temperature is increased to 250°C at a heating rate of 0.5°C / min and kept at 700min, the temperature is increased to 340°C at a heating rate of 0.5°C / min and kept at 700min, the temperature is decreased to 100°C at a cooling rate of 4°C / min, and then cooled with the furnace; The degreasing curve in air atmosphere is: starting from room temperature, heating up to 130℃ at a heating rate of 0.6℃ / min and keeping it for 220min, heating up to 250℃ at a heating rate of 0.6℃ / min and keeping it for 220min, heating up to 340℃ at a heating rate of 0.6℃ / min and keeping it for 340min, heating up to 400℃ at a heating rate of 0.6℃ / min and keeping it for 340min, heating up to 700℃ at a heating rate of 0.6℃ / min, heating up to 1000℃ at a heating rate of 1℃ / min, cooling down to 100℃ at a cooling rate of 4℃ / min, and then cooling with the furnace; The sintering was carried out in an air atmosphere sintering furnace. The specific sintering curve was as follows: a heating rate of 4.5°C / min from room temperature to 1200°C, a heating rate of 3.5°C / min from 1200°C to 1650°C, keeping at 1650°C for 180 min, a cooling rate of 4°C / min from 1650°C to 1200°C, a cooling rate of 5°C / min from 1200°C to 500°C, and then cooling with the furnace.
Claims
1. A method for photocuring and printing mother-of-pearl alumina composite ceramics based on alumina platelets adsorbing SiO2, characterized in that: The steps include: 1) Disperse SiO2 and alumina flakes evenly in distilled water respectively, then mix the two solutions and stir to allow SiO2 and alumina flakes to be fully electrostatically adsorbed; 2) After the mixed solution is allowed to stand and separate into layers, the upper clear liquid is removed for vacuum filtration, and then placed in an oven for drying; the dried ceramic powder is pre-sintered to obtain alumina platelets that adsorb SiO2; 3) preparing ceramic slurry; 4) Using photocuring technology, the ceramic slurry prepared in step 3) is irradiated with ultraviolet light, so that the alumina platelets adsorbed with SiO2 powder are oriented under the action of shear force due to the flow of the slurry, and the slurry in the exposed area is quickly solidified by ultraviolet light irradiation, thereby printing a mother-of-pearl alumina composite ceramic blank; 5) The printed ceramic blank is degreased and sintered under a specific temperature curve to obtain an alumina composite ceramic with a mother-of-pearl structure.
2. The method for photocuring printing of mother-of-pearl alumina composite ceramics based on alumina platelets adsorbing SiO2 according to claim 1 is characterized in that: In step 1), the composition ratio and mixing time of alumina flakes for adsorbing SiO2 are as follows: 0.5g-1.5g of silicon dioxide is added to every 30ml of distilled water, and 1g-3g of alumina flakes is added to every 90ml of distilled water, and then they are placed in an ultrasonic oscillator and mixed for 10 min-30min respectively; then the two solutions are mixed and stirred for 2-3 hours using a digital constant temperature magnetic stirrer; The added SiO2 powder is a monodisperse spherical powder with a particle size of 70nm-300nm, an aluminum oxide platelet width of 4μm-15μm, and a thickness of 200nm-300nm.
3. The method for photocuring printing of mother-of-pearl alumina composite ceramics based on alumina platelets adsorbing SiO2 according to claim 1 is characterized in that: In step 2), the standing time is about 30 min-60 min; the adsorbed ceramic powder is dried at a drying temperature of 150° C.-200° C. for 1 h-2 h; A box-type muffle furnace is used in the pre-sintering process, and the sintering process is: room temperature-1200℃ with a heating rate of 20℃ / min-60℃ / min; 1200℃-400℃ with a cooling rate of 1℃ / min-2℃ / min, keeping at 400℃ for 4h-6h, and then cooling with the furnace.
4. The method for photocuring printing of mother-of-pearl alumina composite ceramics based on alumina platelets adsorbing SiO2 according to claim 1, characterized in that: Step 3) is specifically as follows: first, two dispersants are added into the ceramic slurry liquid phase system and put into a planetary ball mill for ball milling to completely dissolve the dispersants; then, spherical alumina particle powder and a sintering aid are added, and the ball milling is continued until the alumina particles are evenly dispersed in the liquid phase; after taking out the grinding balls, the alumina platelet-adsorbed SiO2 powder prepared in step 2) is added and continued to be evenly dispersed using the ball mill; then, an ultraviolet light initiator is added and stirred evenly; finally, a defoaming treatment is performed under vacuum to obtain a mother-of-pearl alumina composite ceramic slurry.
5. The method for photocuring printing of mother-of-pearl alumina composite ceramics based on alumina platelets adsorbing SiO2 according to claim 4, characterized in that: In step 3), the ceramic slurry liquid phase system consists of 50-60 vol% of 1,6-hexanediol diacrylate accounting for 50-60 vol% of the total volume of the liquid phase, 30-35 vol% of polypropylene glycol 200 accounting for 30-35 vol% of the total volume of the liquid phase, 5-7.5 vol% of trimethylolpropane triacrylate accounting for 5-7.5 vol% of the total volume of the liquid phase, and 5-7.5 vol% of polyethylene glycol (400) diacrylate accounting for 5-7.5 vol% of the total volume of the liquid phase; Or the ceramic slurry liquid phase system is composed of 1,6-hexanediol diacrylate accounting for 55-65 vol% of the total volume of the liquid phase, polypropylene glycol 400 accounting for 25-35 vol% of the total volume of the liquid phase, and trimethylolpropane triacrylate accounting for 5-10 vol% of the total volume of the liquid phase; The added spherical alumina particle powder is 15-30vol% of the ceramic slurry, and the particle diameter is 1-3μm; the added alumina platelet adsorbed SiO2 powder is 15-30vol% of the ceramic slurry; The added sintering aids are MgO and CaO accounting for 3wt% of the SiO2 powder adsorbed by the alumina platelets, and the mass ratio of the mixture is 1:1; The two dispersants added are CC42 accounting for 0.4-0.6wt% and KD1 accounting for 2-3wt% of the total weight of spherical alumina particle powder and alumina platelet adsorbed SiO2 powder, and the mixing ratio is 1:5; the ultraviolet light initiator added is TPO accounting for 2 wt% of the mass of the ceramic slurry liquid phase system; the ratio of added grinding balls is 6-10 zirconia grinding balls with a diameter of 5mm-15mm for every 50ml of slurry.
6. The method for photocuring printing of mother-of-pearl alumina composite ceramics based on alumina platelets adsorbing SiO2 according to claim 1, characterized in that: In step 4), the exposure time of the light-curing printing process is 3 s -8 s, the light-off time is 2 s -10 s, and the exposure power is 2.48 mW / cm 2 -7.95mW / cm 2 The thickness of each layer is 0.03 mm -0.08 mm, and the lifting speed of the workbench is 0.5 mm / s -1.5 mm / s.
7. The method for photocuring printing of mother-of-pearl alumina composite ceramics based on alumina platelets adsorbing SiO2 according to claim 1, characterized in that: In step 5), the degreasing process is divided into two parts, first degreasing in an argon atmosphere, and then degreasing in an air atmosphere; The degreasing curve under argon atmosphere is as follows: starting from room temperature, the temperature is increased to 100-130°C at a heating rate of 0.2°C / min-0.5°C / min, and the temperature is kept for 600-700min; the temperature is increased to 220-250°C at a heating rate of 0.2°C / min-0.5°C / min, and the temperature is kept for 600-700min; the temperature is increased to 310-340°C at a heating rate of 0.2°C / min-0.5°C / min, and the temperature is kept for 600-700min; the temperature is decreased to 100°C at a cooling rate of 2°C / min-4°C / min, and then cooled with the furnace; The degreasing curve in air atmosphere is: starting from room temperature, adopt a heating rate of 0.3-0.6℃ / min to increase to 100℃-130℃ and keep warm for 120 min-220min, adopt a heating rate of 0.3℃ / min-0.6℃ / min to increase to 220℃-250℃ and keep warm for 120 min-220min, adopt a heating rate of 0.3℃ / min-0.6℃ / min to increase to 310℃-340℃ and keep warm for 240min-340min, adopt a heating rate of 0.3℃ / min-0.6℃ / min to increase to 370℃-400℃ and keep warm for 240 min-340min, adopt a heating rate of 0.3℃ / min-0.6℃ / min to increase to 600℃-700℃, adopt a heating rate of 0.5℃ / min-1℃ / min to increase to 1000℃, adopt a heating rate of 2℃ / min The temperature was lowered to 100°C at a cooling rate of -4°C / min and then cooled in the furnace.
8. The method for photocuring printing of mother-of-pearl alumina composite ceramics based on alumina platelets adsorbing SiO2 according to claim 7, characterized in that: In step 5), sintering is carried out in an air atmosphere sintering furnace, and the specific sintering curve is: room temperature-1200°C adopts a heating rate of 4°C / min-4.5°C / min, 1200°C-1650°C adopts a heating rate of 3°C / min-3.5°C / min, 1650°C is kept for 120min-180min, 1650°C-1200°C adopts a cooling rate of 3°C / min-4°C / min, 1200°C-500°C adopts a cooling rate of 4°C / min-5°C / min, and then the alloy is cooled in the furnace.
9. Based on the photocuring printing of SiO2 adsorbed by alumina platelets, the mother-of-pearl alumina composite ceramics are characterized by: The method is prepared according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method for printing oriented lamellar alumina reinforced ceramic through surface exposure based on micro-channel
CN114477967A
Mixed buried powder degreasing method based on photocuring 3D printing texture aluminum oxide
CN115010471A
Additive manufacturing method for improving compactness and product thereof
CN117534447A
Method for photocuring 3D printing of mother-of-pearl ceramic with random geometric mosaic interface
CN118184341A
Preparation method of mullite ceramic based on photocuring molding 3D printing
CN118771869A